Bioactivity of Biphasic Calcium Phosphate Granules, the Control of a Needle-Like Apatite Layer Formation for Further Medical Device Developments - d’Arros, Cyril; Rouillon, Thierry; Veziers, Joelle; Malard, Olivier; Borget, Pascal; Daculsi, Guy (Frontiers in Bioengineering and Biotechnology, 2020)
Biphasic Calcium Phosphate bioceramics (Hydroxyapatite/TriCalciumPhosphate, HA/TCP) for tissue engineering and Drug Delivery Systems is a unique know-how. A mechanical mixture of HA and TCP does not lead to such bioactive ceramics. The wet elaboration conditions of Calcium Deficient Apatite CDA or CDHA followed by sintering, converts it into TCP and HA. The dissolution precipitation of nano sized needle-like crystals at the surface of BCP occurs on time at body temperature. Combining several technics of characterization (SEM, TEM, EDX, BET, chemical analysis, XRD, FTIR), we demonstrated an evolution on time of the HA/β-TCP. The current paper describes the crystallographic evolution of initial β-TCP rhomboedric crystallogaphic structure to micro sized needle-like layer corresponding to apatitic TCP form. This phenomenon leads to an increase of the HA/TCP ratio, since hexagonal apatitic-TCP is similar to hexagonal HA. However, the Ca/P ratio (reflecting the chemical composition HA/TCP) remains unchanged. Thus, the high reactivity of BCP involves dynamic evolution from rhomboedric to hexagonal structure, but not a chemical change. The dynamic process is reversible by calcination. These events are absolutely necessary for SMART Scaffolds in Bone Regeneration and Orthobiology.